Prediction of the number of births in the Governorate of Basra for the period (1998-2050) - عايد, ناديه علي (Journal of Economics and Administrative Sciences, 2020)
The adoption of many mathematical concepts contributes to the construction of models of sports and the population can be interpreted to explain the movement and growth of the population lead to proper planning to manage the requirements of the population and meet their needs of providing education or providing medical services, health and others. In this study, the number of births in the Governorate of Basrah for the period (1998-2050) is estimated to be based on the assumption that the population of the visually impaired is a stable society. If the rate of growth is (0.0492), some demographic indicators are important for maintaining the average age of women at pregnancy (27.817). Each woman will give birth (3.74) female birth during her reproductive life.  And the total fertility rate in the province (3.738795), in addition to proving that the population of the visually impaired population is increasing.